Analisis Pengembangan Nilai Agama dan Moral Anak Usia 5-6 Tahun - Radhiyatul Fithri; Baidarus; Ariani, Niken (JURUSAN PENDIDIKAN GURU PENDIDIKAN ANAK USIA DINI, 2023)
The purpose of this study was to analyze and determine the religious and moral values ​​of children. This research method is qualitative used to explain the data from the research results and describe what it is about the Analysis of Children's Religious and Moral Values. Planning is compiled and designed systematically and then analyzed qualitatively and presented in the form of a research report. The results of the research that has been done, it is concluded that based on the results of the research that has been done, it can be concluded that the development of religious and moral values ​​in children in Muara Kasih Kindergarten as a whole has several indicators that are not optimal. The delay in the development of religious and moral values ​​in children in Muara Kasih Kindergarten is due to several factors, both from within the child itself and also from the environment around the child. The role of a teacher in efforts to develop the development of religious and moral values ​​in children can be done by encouraging, guiding, and motivating their students so that they are able to further develop the development of religious and moral values ​​and parents can provide good examples or examples, in behavior and etc. Keywords: